FAKTOR‐FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERBANKAN INDONESIA - FARAH MARGARETHA; MARSHEILLY PINGKAN ZAI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
This research is performe on order to test the influence of the variable Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Biaya Operasional/Pendapatan Operasional (BOPO), Non Performing Loan (NPL) and Net Interest Margin (NIM) towards Return on Asset (ROA). The population used in this study is Indonesia public Bank in the period of 2007-2011. Data analysis with multiple regression. This result of research shows that CAR, LDR, BOPO, NPL and NIM positive significant influence toward ROA in Indoensiapublic Bank. The implication of this study is that the bank’s management and investors can improve financial performance with respect to the bank’s financial ratios to keep it in the category of healthy banks.